Conceptualising the Value of Life in Bioethical Discourse: Sanctity vs Quality of Life - Horban, Oleksandr; Martych, Ruslana (Studia Warmińskie, 2023)
The article deals with the problem of the value of life in the context of its understanding in bioethical discourse. Two different approaches are used to discuss the topic. The first approach demonstrates a set of imperatives of human behaviour associated with the dominance of the religious component defining the value of life. It is called the concept of the “sanctity of life” and considers human life as a sacred act of divine influence on the existence of the living. The second approach systematises bioethical views that promote the supreme value of freedom and autonomy in making decisions by each individual, including those related to their life and health. It is called the concept of “quality of life” and represents a set of ideas that suggest to consciously influence the state of life of the individual if it is possible to improve it or if its further existence loses its rational meaning. Being in opposition to each other, these two main conceptual approaches create a problematic situation that stimulates scientific interdisciplinary research within the framework of bioethical discourse, forming its conceptual and categorical apparatus and expanding the worldview of the researcher and the reflective individual.